Measurement of nitric oxide metabolites in brain microdialysates by a sensitive fluorometric high-performance liquid chromatography assay - Woitzik, Johannes; Abromeit, Nils; Schaefer, Franz (Analytical biochemistry, 2002)
Nitric oxide (NO), formed from arginine by a specific neuronal NO synthase, is an important neurotransmitter in various regions of the central nervous system. While intracerebral microdialysis is an elegant technique to study local extracellular neurotransmitter concentrations in vivo, NO metabolites (nitrate, nitrite (NOx)) are difficult to study at high temporal resolution because of low tissue concentrations and small sample volumes. We developed a sensitive fluorometric high-performance liquid chromatography (HPLC)-coupled NOx assay adapted for the use in brain microdialysate samples.
Available online 25 May 2002
Gesehen am 10.12.2020